Funções dos músculos do assoalho pélvico em mulheres continentes e em mulheres incontinentes - Raquel Rodrigues Gontijo (2012)
The literature clearly reports the relation between pelvic floor muscles (PFM) and the urinary incontinence mechanism. PFM training has been recommended as the first line treatment for urinary incontinence. However, evidence regarding the PFM functions in continent and incontinent women including muscle strength, endurance, contraction ability and coordination is lacking. Most studies do not investigate allPFM functions, neither the association of those with the urine loss on effort symptom. In addition, few studies describing the PFM function in a cohort of continent women. Therefore, to improve the understanding of the continence mechanism, which may lead to more successful therapeutic approaches to incontinent women, this study aimed to describe the PFM functions in women with or without urinary incontinenceand to investigate if there is any difference between continent and incontinent women regarding to these functions. Materials and Methods: Cross-sectional observational study with continent and incontinent women. Sociodemographic, clinical data and PFM functions were investigated. Perioneometry (Peritron®) was used to measure muscle strength and vaginal palpation was used to measure muscle resistance,contraction ability and coordination. The data collected in the assessments were statistically analyzed by a descriptive analysis. The descriptive data and the PFM functions were compared between groups by the Mann Whitney and by the chisquare tests. Results: The continent and the incontinent group included 86 and 75 participants respectively. There was a significant difference in all PFM functions investigated (P<0.01), even after controlling for possible confounding factors. Formuscle strength, the incontinent group (median=26 cmH2O) showed significant higher values of muscle strength compared to continent group (median=37.30 cmH2O, p=0.006). For muscle resistance, the incontinent group (median=22 sec.) showed significant worse resistance compared to the continent group (median= 30 sec. p=0.002). The chance to identify participants without the contraction ability in the incontinent group was 6.06 (2.17 16.67; p = 0.001) times higher than the continent group and the chance to observe participants without coordination in the incontinent group was 55.76 (12.7 243.8; p = 0.000) times higher than in the continent group. There was a predominant use of abdominal muscle in both groups. Conclusion: This study showed that there is difference between continent and incontinent women in all PFM functions. This study results inform physiotherapists the values related to PFM strength and endurance, in continent and incontinent women. Furthermore, the difference in PFM contraction ability and coordination in these two groups found in this study suggest that future studies and clinical approachof stress incontinence focusing on these aspects are warranted.